Marrying well : the clinician's guide to premarital education - Bruun, Elena Lesser; Ziff, Anne F. (New York : W.W. Norton, 2010)
From the Publisher: This book is aimed both at experienced therapists who wish to expand into this area of practice, and novice premarital counselors and couple therapists who need to understand the unique challenges and issues faced by premarital couples in the twenty-first century. Separate chapters discuss how to recognize key factors in individuals and couples that predict long and happy marriages (such as empathy, flexibility, shared goals, and the ability to make each other laugh), and the most common issues presented by couples in premarital counseling and how best to address them, such as: differing racial, cultural, and ethnic backgrounds; differences in religious beliefs and attitudes; sexual issues; money; and disagreements about whether to have or how to raise children. Here, the therapist will also learn how to help clients decide whether or when to get married, how to help couples deal with the stress and issues brought on by wedding planning-and how to work with couples whom the therapist thinks might be better off not getting married. Bruun and Ziff rely on their combined decades' worth of clinical experience, presenting numerous case studies that illustrate the variety of couples seeking premarital counseling today. The result is an excellent introduction to contemporary premarital counseling that offers sage advice and practical approaches to working with couples dealing with contemporary premarital challenges.
Acknowledgments -- 1: Premarital counseling: an introduction -- 2: Looking backward: a brief foray into the history of marriage and marriage counseling -- 3: Lay of the land: current research and practice -- 4: Who is your client? -- 5: Common premarital problems -- 6: What predicts a satisfying marriage: individual factors -- 7: Couple predictors of marital satisfaction and stability -- 8: Eight premarital stages -- 9: Summary and a not-so-modest proposal -- References -- Index.
"A Norton professional book."
Includes bibliographical references and index.
Keywords: Marriage counseling; Couples -- Counseling of; Marriage